Women's Pornography Consumption, Alcohol Use, and Sexual Victimization. (August 2021) - de Heer, Brooke; Prior, Sarah; Fejervary, Jenna
While research in recent years has investigated the influence of pornography consumption on sexually aggressive behavior, research on the relationship between pornography and experienced victimization is sparse. The current study sought to explore female sexual victimization and its relationship with pornography consumption and alcohol use at two universities ( N = 483). Binary logistic regression analyses indicate that both pornography and alcohol consumption were unique predictors of self-reported victimization for college females and that the combined effect of pornography and alcohol dramatically increases the odds of victimization. Results are discussed in the context of pornography's impact on the minimization of sexually aggressive acts in real life and campus rape culture.